2000
DOI: 10.1071/pp99097
|View full text |Cite
|
Sign up to set email alerts
|

Defensive strategies against high light stress in wild and D1 protein mutant biotypes of Erigeron canadensis

Abstract: The Ser264ÆGly substitution on the D1 protein is accompanied by a higher photosensitivity of the mutant plant. This may be due to an increased D1 protein turnover and/or to a lower xanthophyll cycle activity in vivo. The relative importance of these two photoprotective mechanisms in wild and D1 protein mutant biotypes of Erigeron canadensis L. was established by using dithiothreitol and streptomycin. Moreover, the interconversion of violaxan-thin to zeaxanthin via antheraxanthin was studied in isolated thylako… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 39 publications
2
15
0
3
Order By: Relevance
“…Previous investigations have shown that plants that are mutants in the D1 protein function, with a lower ability to maintain the proton motive force due to an impaired electron transport, have a lower ability of non-photochemical quenching [27,28]. These circumstances raised the question if the non-photochemical quenching properties in Ulva spp can be negatively affected at photoinhibitory conditions.…”
Section: Introductionmentioning
confidence: 94%
“…Previous investigations have shown that plants that are mutants in the D1 protein function, with a lower ability to maintain the proton motive force due to an impaired electron transport, have a lower ability of non-photochemical quenching [27,28]. These circumstances raised the question if the non-photochemical quenching properties in Ulva spp can be negatively affected at photoinhibitory conditions.…”
Section: Introductionmentioning
confidence: 94%
“…Gly (S264G) D1 protein mutation were found to have lower quantum yield of PSII (U PSII ), linear electron transport rate (ETR), light-induced photochemical quenching coefficient (qP), and they proved defective in non-photochemical quenching (NPQ) capacity as well as having an altered xanthophyll cycle pattern as compared with the wild-type plants (Curwiel and van Rensen 1996;Darkó et al 1996Darkó et al , 2000Sundby et al 1993;Váradi et al 1994Váradi et al , 2003. The highly conserved D1 protein is encoded by the psbA gene in the chloroplast-DNA (Morden and Golden 1989).…”
Section: Introductionmentioning
confidence: 98%
“…Kimutatták továbbá, hogy az AR biotípusokban nagyobb sebességgel működik a D1 protein degradációs/helyreállítási folyamata (turn over) (Sundby et al, 1993a;Darkó et al, 2000). Elképzelhetőnek tartják, hogy a magasabb fényérzékenység a megemelkedett D1 protein turn over-nek (Sundby et al, 1993a) és/vagy in vivo a xantofill ciklus alacsonyabb aktivitásának (Váradi et al, 1994;Darkó et al, 1995) köszönhető.…”
Section: A Hidrogénhíd Kötéseket Szaggatott a Hidrofób Kölcsönhatástunclassified
“…folyamata az AR gyomokban (Sundby et al, 1993a;Darkó et al, 2000) maga után vonhat egy megnövekedett ATP igényt, ami az ATPáz enzimen keresztül magasabb proton effluxot eredményezhet, mely szintén hozzájárulhat a tilakoid membránon keresztüli proton gradiens kiépülésének csökkenéséhez. Ez magyarázatot adhat a 20%-kal alacsonyabb xantofill deepoxidációra, amely pedig hozzájárulhat a qE csökkenéséhez.…”
Section: Eredmények Megvitatásaunclassified
See 1 more Smart Citation